Tiga Model Ratapan Dalam Syair Arab Analisis Semiotik Puisi Burikta Ya Qabra Ar-Rasuli Karya Hassan Bin Tsabit - Rahman Zaenuri, Riza; Alim, Muhammad (Middle Eastern Culture & Religion Issues, 2022)
This study discusses the poetry of Hassan bin Thabit's best friend, a figure known by his nickname as a “Prophet’s Poet” when mourning the death of the Prophet through his poem entitled “Burikta ya qabra ar-rasuli” using Riffaterre's semiotic theory approach. The purpose of this study is to describe the features and characteristics of the three models of lamenting poetry in the Arabic tradition, as well as to strengthen the opinion which states that lamentation poetry is a the most honest poetry from the poet's point of view or his feel. as this is what distinguishes it from all other types of Arabic poetry such as madh and hija’. The results show that the three models of lamentation in Hasan's ratsa` poetry have the following features and characteristics: 1) An-nadbu: is an expression form of sadness through the atlal method, namely mentioning objects and places that are related to the dead.. 2) At-ta`bin: is a flattery expression to the dead by mentioning some commendable traits and behavior during his factual life 3) Al-‘aza`: which is a way and comforting expression for relatives and people who have a direct relationship with the dead.